Clinical, biochemical, and molecular genetic characteristics of patients with primary carnitine deficiency identified by newborn screening in Shanghai, China - Chang, Siyu; Yang, Yi; Xu, Feng; Ji, Wenjun; Zhan, Xia; Gao, Xiaolan; Chen, Ting; Qiu, Wenjuan; Zhang, Huiwen; Liang, Lili; Lu, Deyun; Zhang, Kaichuang; et al. (Frontiers in Genetics, 2022)
Background: Primary carnitine deficiency (PCD) is an autosomal recessive disease caused by mutations in the SLC22A5 gene, and it encodes the organic cation transporter 2 (OCTN2). Patients with PCD may be at risk of skeletal or cardiac myopathy, metabolic decompensation, and even sudden death. This study aimed to analyze the biochemical, clinical, and genetic characteristics of PCD patients identified by newborn screening (NBS) in Shanghai. Methods: Dried blood spot (DBS) samples of newborns were analyzed through tandem mass spectrometry (MS/MS) from January 2003 to December 2021. Newborns with low free carnitine (C0) levels were recalled. Mutation in the SLC22A5 gene was analyzed on suspected positive newborns with low C0 levels after recall. Results: 1,247,274 newborns were screened by MS/MS and 40 newborns were diagnosed with PCD, therefore the incidence of PCD in Shanghai was approximately 1:31,200. The mean C0 level in newborns with PCD was 5.37±1.79 µmol/L before treatment and increased to 24.45±10.87 µmol/L after treatment with L-carnitine. Twenty-three different variants were identified in the SLC22A5 gene, including 8 novel variants, of which c.51C>G (p.F17L) was the most frequent (27.27%, 18/66), followed by c.1400C>G (p.S467C) (25.76%, 17/66). Almost all the screened PCD patients were asymptomatic. Conclusion: NBS via MS/MS was a quick and efficient method for the early diagnosis of PCD. The incidence of PCD in Shanghai was 1:31,200. Eight novel variants were identified, which greatly expanded the variant spectrum of SLC22A5. MS/MS combined with genetic testing could effectively improve the diagnostic accuracy of PCD.